Comportamento inovador e inovação social de produtores da agricultura familiar: validação da escala ISP-AF - Flores, Raquel Dalvit (2023)
Family farming emerged from the struggles for recognition and rights proposed by a multitude of subjects, mainly by the movements and union marches in the countryside. This movement to spread innovative culture in the agricultural environment, causes changes in attitudes and behaviors resulting in a greater ability of managers to manage their agricultural businesses (ALVES, 2016). In this sense, this study aimed to analyze influence of the innovative behavior of Brazilian family farmers and its relationship with social innovation. The innovative behavior scale proposed and adapted by Van der Vegt and Janssen (2003) was used; Kanter (1988); Reis and Carvalho (2003); Jong and Hartog (2008) and Axtell et al. (2000). A scale was constructed and validated to measure levels of social innovation for family farmers using the Delphi technique and relevant statistical analyses. In this way, it was possible to carry out a survey consisting of three instruments: a sociodemographic questionnaire, the scale built for social innovation and a scale on innovative behavior. The invariances between genders on the Social Innovation scale were also analyzed and, as soon as, the proper relationships between innovative behavior and social innovation were established using the modeling of structural equations. The survey covered family farmers in the states of Rio Grande do Sul, Santa Catarina and Paraná, in which 264 questionnaires were collected and analyzed using Structural Equation Modeling with Partial Least Squares Estimation (PLS-SEM) and using the software algorithm SmartPLS® version 3.3.9 (RINGLE; WENDE; BECKER, 2015). As a result, the proposed scale model is effective and supported by the confirmation of the hypotheses and, therefore, can be considered to verify the social innovation of family farmers. In this research, it was possible to infer that family farmers have an innovative behavior of moderate to high intensity and are more oriented to the dimensions of Innovative Results and External Contacts, presenting a significant relationship with all dimensions of social innovation, namely generation of ideas, opportunities, challenges, building and implementing and growing and moving up. That is, the farmer's innovative behavior directly influences his social innovation practices. The dimension of participatory leadership within the theme of innovative behavior showed a strong relationship only with the dimension of opportunities, with the other dimensions generation of ideas, challenges, building and implementing and growing and rising its relationship was insignificant. Social innovation, in turn, had moderate to high intensity, where respondents mention more attention to winning new customers, new opportunities and acquiring better equipment and technology.